Does experiential marketing alone encourage domestic tourists to revisit? Evidence from a tourist destination in West Java, Indonesia - Ratnamiasih, Ina; Wasito, Wasito; Baihaqi, Muhammad Iqbal; Andriyani, Mira (University of Islam Malang, 2024)
The sustainable growth of tourist destinations relies heavily on revisit intention. Retaining repeat tourists is not only more economical but also about five times more profitable than attracting new ones. A dominant paradigm in tourist behavior literature shows a sequential relationship among image, quality, satisfaction, and post- behavior. Few studies have examined experiential marketing as a determinant of revisit intention. This study aims to extend the literature by investigating the effects of service quality and experiential marketing on revisit intention, with tourist satisfaction as a mediator. A total of 166 responses from domestic tourists who visited Purwakarta, West Java, Indonesia, were analyzed using PLS-SEM. The results confirmed the positive effects of service quality and experiential marketing on tourist satisfaction. Interestingly, the mediating role of tourist satisfaction was only partial, as the direct relationship between experiential marketing and revisit intention was not supported. Experiential marketing might enhance specific aspects of the tourist experience, providing immediate and short-term positive effects that influence satisfaction directly after the visit. However, overall satisfaction encompasses a broader evaluation of the entire trip, integrating various elements and lasting impressions that collectively drive the intention to revisit.